THE STRATEGIC ROLE OF LEGAL EDUCATION IN SHAPING AGENTS OF CHANGE IN HIGHER EDUCATION INSTITUTIONS - Nurita, Riski Febria; Laila, Khotbatul (Four Son Scholarship, 2026)
Legal education plays a pivotal role in shaping students not only as legal professionals but also as agents of change capable of contributing to social transformation and the strengthening of the rule of law. This study aims to analyze the strategic role of legal education in higher education institutions from a normative juridical perspective, focusing on how legal norms, principles, and concepts mandate and frame the transformative function of legal education. Employing normative legal research, this study applies the statute approach and the conceptual approach. The statute approach is used to examine constitutional provisions, higher education laws, and regulations governing national education that emphasize character development, legal awareness, and civic responsibility. The conceptual approach is utilized to analyze key doctrines and legal concepts such as legal education, legal consciousness, justice, and agent of change within the framework of legal theory and educational philosophy. The results of the study demonstrate that legal education is normatively positioned as a strategic instrument for internalizing legal values, fostering critical legal reasoning, and cultivating ethical responsibility among students. Legal norms implicitly and explicitly require higher education institutions to integrate legal education that goes beyond technical legal knowledge and contributes to the formation of socially responsive and justice-oriented graduates. However, the study also identifies a normative gap between the objectives articulated in legal norms and the implementation of legal education, which often remains dominated by positivistic and doctrinal teaching models. This study concludes that strengthening legal education as a means of forming agents of change is a constitutional and statutory imperative. Normative reorientation toward value-based, ethical, and socially grounded legal education is essential to ensure coherence between legal ideals and educational practice in higher education institutions.